Media Pembelajaran Interaktif dan Kepuasan Mahasiswa Selama Pandemi Covid-19 - Murbiah Murbiah; Maya Fadlilah; Paray Theo Lonando; Zairinayati Zairinayati (Jurnal Penelitian Kesehatan SUARA FORIKES, 2022)
Efforts to reduce the spread of Covid-19 in the education sector are by implementing online learning. Some online learning media are interactive media and e-learning. Student satisfaction in the online learning process is very important to increase student motivation and achievement during the Covid-19 pandemic. The purpose of this study was to determine the difference in student satisfaction between the use of interactive learning media without a network and with a network during the Covid-19 pandemic. This study was applied with a cross-sectional design. The sample is Semester IV students of the Nursing Science Study Program who take maternity nursing courses. This study compares the difference in satisfaction of 2 groups, each of which is learning with a network and without a network. The results of the analysis show that the average satisfaction of the interactive learning group without the network is 34.36 and with the network is 33.38. The results of the comparison test show the value of t = 3.040 with a value of p = 0.003. It was concluded that there was a difference in student satisfaction between those using interactive media without a network and with a network.Keywords: satisfaction; interactive media; network; Covid-19 pandemic ABSTRAK Upaya pengurangan penyebaran Covid-19 pada bidang pendidikan adalah dengan memberlakukan pembelajaran daring. Beberapa media pembelajaran daring adalah media interaktif dan e-learning. Kepuasan mahasiswa dalam proses pembelajaran daring sangat penting untuk meningkatkan motivasi dan prestasi mahasiswa selama pandemi Covid-19. Tujuan penelitian ini adalah untuk mengetahui perbedaan kepuasan mahasiswa antara penggunaan media pembelajaran interaktif tanpa jarigan dan dengan jaringan selama masa pandemi Covid-19. Penelitian ini diterapkan dengan desain cross-sectional. Sampel adalah mahasiswa Semester IV Program Studi Ilmu Keperawatan yang mengambil mata kuliah keperawatan maternitas. Studi ini membandingkan perbedaan kepuasan 2 kelompok, masing-masing adalah pembelajaran dengan jaringan dan tanpa jairngan. Hasil analisis menunjukkan bahwa rerata kepuasan kelompok pembelajaran interaktif tanpa jaringan adalah 34,36 dan dengan jaringan adalah 33,38. Hasil uji komparasi menunjukkan nilai t = 3,040 dengan nilai p = 0,003. Disimpulkan bahwa ada perbedaan kepuasan mahasiswa antara yang menggunakan media interaktif tanpa jaringan dan dengan jaringan.Kata kunci: kepuasan; media interaktif; jaringan; pandemi Covid-19